The Karawitan Contemporary “Ngontang Gambang” | Karya Karawitan Kontemporer “Ngontang Gambang” - I Gede Agung Surya Negara (GHURNITA: Jurnal Seni Karawitan, 2023)
Ngontang Gambang by definition has a meaning and message that the stylist feels, namely the difference that if put together will produce something new. Ngontang as a source of imagination and pouring ideas that will be able to translate an event that is felt by the stylist and poured into a medium reveals gamelan Gambang by offering ideas of thought through works of art. This contemporary music work of Ngontang Gambang focuses on Gambang gamelan or tingklik (Balinese) which uses 3 pairs of Gambang gamelan and 5 Kendang. The process of creating this work uses three stages, namely the exploration stage (Exploration), the experimental stage (Improvisation), and the formation stage (Forming). Ngontang Gambang's contemporary music work consists of three main parts, namely part one, part two, and part three. This work is supported by 7 (seven) growers from Sanggar Mekar Seruni with a duration of approximately 12 minutes.